A fronteira negociada: índios e espanhóis nos confins meridionais do império (século XVIII) - Silva, Juliana Aparecida Camilo da (Universidade do Vale do Rio dos Sinos, 2016)
This work proposes to understand the relationships that native groups from the southern Pampa bonaerense and the "Spanish" stablished during the Eighteenth century. The natives groups called "pampas" and "serranos" were outside the jurisdiction of the Buenos Ayres' authorities, but centuries of previous contacts with westerners, as well as with groups "transcodilleranos", had already transformed the cultural, social and economical agenda of those natives. The Salado River was turned into a natural border, on that period, between the natives and the westerners from Buenos Ayres and its hinterlands. In 1740, the so far pacific relationships between those two worlds changed radically. The criollos started to expand their properties in the tierra adientro. In order to make such expasion feasible, they used different policies towards the native population of the area, such as Jesuit missions, treaties and the militarization of the border. Thus, by analyzing this microcosmos inside the Spanish empire, we intend to uncover how the natives positioned themselves in face of such an open conjuncture, especially regarding the three Missions settled by the Jesuits in the area. These missions are considered here as part of a wider reality, which is the border's reality. To build the narrative that will structure this work, we will follow the trajectory of a serrano chief, "Cangapol", also known by the Spanish as "Bravo", who was a leading figure in important events that took place on that space during the Eighteenth century. The chief "Bravo" appears as one of the agents that motivated the constitution of the reductions, and on the other hand, after they are already settled, he once again becomes a leading character, now having the role of making demands, until, eventually, his attacks ended up destroying the pueblos. It is through this character - that shall work as our narrative point - that we will examine this border panorama in order to think of the natives as historical subjects of this process. The metodology for this work is going to be the reading of the reference literature and the research of primary sources. They will be analyzed using theoretical contributions that suggest the relevance of giving importance to the native agency.
Keywords: Agência indígena; Fronteira; Missões autrais; Border; Native agency; Cangapol; Southern missions; ACCNPQ::Ciências Humanas::História